Asian development after the Asian Drama - Richard Kozul-Wright; Daniel Poon (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Inspired by Gunnar Myrdal's core concepts discussed in his seminal work, Asian Drama: An Inquiry into the Poverty of Nations, published in 1968, this paper analyses the opening-up experiences of three Asian countries (China, India, and Malaysia) by triangulating between the following: (i) the orientation of selected policy tools in trade, technology, investment, and finance in shaping a country's degree of economic openness; (ii) the rational coordination of operational controls of these policy tools to achieve stated objectives; and (iii) the overall development trends observed in the Asia region. The "rational coordination of operational controls" is interpreted with reference to the strategic use of selected policy tools in the historically successful cases of earlier East Asian industrialization. Under this framework, the paper contends that divergence in Asian growth experiences can be understood by variations in institutional capabilities to address market and firm-level (and government) failures in the catch-up process, and the pragmatic experimentation by policymakers in search of more effective institutional mechanisms - carrots, sticks, and competitive pressures - in pursuit of desired development outcomes.
Keywords: F63; B52; O25; O53; 330; economic openness; operational controls; strategic integration